Outcomes after noncardiac surgery in patients with left ventricular assist devices: a systematic review - Alamouti-Fard, Emad; Garg, Pankaj; Yazji, John; Brigham, Tara; Jacob, Samuel; Wadiwala, Ishaq J.; Pham, Si M. (Frontiers in Cardiovascular Medicine, 2024)
Background The number of patients living with left ventricular assist devices (LVADs) has gradually increased in the past decade. Non-cardiac surgery (NCS) in patients with LVAD poses a unique situation with its inherent challenges. Aim We conducted a comprehensive review to investigate the perioperative complications and mortality associated with emergent or elective NCS in patients with LVAD. Method A comprehensive literature search for any papers referring to continuous LVAD patients with NCS. All publications with at least five durable LVAD patients who had NCS were eligible for inclusion. Result Twenty articles matching our criteria were found and included in our study. This systematic review included 6,476 LVAD patients who underwent 6,824 NCS. There were 5–3,216 LVAD patients with NCS in each study. The median age was between 39 and 65 years, and most of the patients (78.8%) were male. Thirty-day postoperative mortality ranged from 0% to 60%. Eight studies reported no death within the 30 days of the operation. Common complications include gastrointestinal (GI) bleeding, intracranial bleeding, infection, acute kidney injury (AKI), urinary tract infection (UTI), stroke, sepsis, pneumonia, and VAD exchange. Emergent abdominal surgery had the highest (up to 60%) mortality rate, and vascular and neurological operations had the highest complication rates. Due to the diverse range of patients in each publication and the combination of outcomes presented in various publications, a meta-analysis was not conducted. Conclusion In LVAD patients, noncardiac surgery may be performed effectively and safely. LVAD patients who undergo non-cardiac surgery may require more transfusions due to their complex coagulopathies. However, perioperative management of LVAD patients undergoing emergent NCS should be optimized to reduce mortality. Systematic Review Registration https://osf.io/fetsb/.